2021
DOI: 10.4082/kjfm.20.0181
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Serum Vitamin D Concentration and Colon Polyp: A Cross-Sectional Study Using Health Care Screening Database in a Tertiary Hospital in Korea

Abstract: Background: As indoor activity increases with modern lifestyles changes, reduced exposure to sunlight may lead to reduced vitamin D synthesis. Previous studies demonstrated that increased vitamin D level is associated with decreased risk of colon cancer; therefore, this study attempted to determine the association between vitamin D and colon polyps, which may be precancerous lesions, in participants who underwent colonoscopy exams.Methods: A total of 31,004 participants who underwent routine health checkups, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A total of 3,129 articles were retrieved from the databases and reference lists during the initial screening process. After a full-text review, 28 studies were included for qualitative analysis, among which four studies reported the same population ( 13 , 14 , 16 , 25 ), so 24 studies were left for meta-analysis ( 15 , 17 , 18 , 26 46 ). Table 1 summarized the basic characteristics of each study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 3,129 articles were retrieved from the databases and reference lists during the initial screening process. After a full-text review, 28 studies were included for qualitative analysis, among which four studies reported the same population ( 13 , 14 , 16 , 25 ), so 24 studies were left for meta-analysis ( 15 , 17 , 18 , 26 46 ). Table 1 summarized the basic characteristics of each study.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D: 10 studies investigated the association between vitamin D and the risk of SPs ( 18 , 28 , 29 , 31 , 34 , 37 , 38 , 42 , 43 , 45 ). The forest plot illustrated a close-to-significant decreased risk of SPs with increased levels of vitamin D intake (OR = 0.95, 95%CI:0.90–1.02), and statistically significant heterogeneity was found ( I 2 = 54.9%; P = 0.018) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study suggested that the inverse association between circulating 25(OH)D and adenomas does not apply to hyperplastic polyps [ 8 ]. However, another study in 2021 did not find evidence for an association between vitamin D and overall colorectal polyps, but observed a trend for decreased odds of hyperplastic polyps with increased vitamin D levels [ 59 ]. The research variables of the above study were quite different from our study, which suggested that Vitamin D deficiency increased the risk of CRPs, especially nonadenomatous polyps.…”
Section: Discussionmentioning
confidence: 99%
“…2A. It is thought that the discrimination power can be improved by learning more data or adding factors such as CBC 24 , blood vitamin D concentration 25,26 , and blood lipid profile 27,28 , which are weak but known risk factors for polyps as it is included in general health examinations.…”
Section: Discussionmentioning
confidence: 99%